Neutrophil accumulation induced by bacterial lipopolysaccharide: effects of dexamethasone and annexin 1 - Allcock, G H (Blackwell Science Inc, 2001)
Annexin 1 (ANX-1) can reduce leucocyte migration in response to cytokines and chemokines in some rodent models of inflammation. However, its effectiveness against an inflammatory stimulus as strong as bacterial lipopolysaccharide (LPS) is unknown. Thus, we have examined whether ANX-1 can modulate LPS-induced neutrophil accumulation in the rat, as assessed by intravital microscopy and by myeloperoxidase (MPO) assay. The anti-inflammatory glucocorticoid, dexamethasone (DEX) was also studied for comparison. LPS superfusion induced adhesion of leucocytes to the endothelium and a subsequent increase in emigration from rat post-capillary venules over 2 h as assessed by intravital microscopy. Either ANX-1 or DEX was able to attenuate this adhesion and emigration of leucocytes. MPO activity in the lung, kidney and ileum was elevated after a 6-h exposure to LPS (intraperitoneal), indicating accumulation of neutrophils in these tissues. DEX attenuated the LPS-induced increase in MPO in the ileum but had no effect on MPO in the lungs or kidneys. This would suggest that the underlying mechanism by which neutrophils accumulate in the ileum, and more generally in the gastrointestinal compartment, is different from other vascular beds. ANX-1 had no effect on the LPS-induced increase in MPO activity in any of the tissues studied. Thus, from these data, ANX-1 appears to reduce leucocyte adhesion and emigration induced by a short-term (2 h), but not a longer (6 h) exposure to LPS.